Performance Analysis of RSA–RC4 Hybrid Encryption Using the EM2B Key Generator - Elwin Purba Elwin; Aji Prabowo; Jesman Ritonga (Universitas Budi Darma, 2026)
This study evaluates the computational performance of a hybrid encryption scheme that combines RSA for key protection, RC4 for file encryption, and the EM2B mechanism for deterministic key expansion. The prototype was implemented as a PHP-based application and tested on 35 SQL text files. RC4 was used as the baseline, while the hybrid scheme was assessed using ciphertext size, character count, encryption time, decryption time, and restoration success. The reported averages show that RC4 required 1.33 s for encryption and 1.41 s for decryption, whereas RSA–EM2B–RC4 required 5.30 s and 100.09 s, respectively. The hybrid scheme also produced approximately 4.29 times greater ciphertext storage than RC4 alone. All files were restored to the same reported size after decryption; however, byte-level or hash-based integrity verification was not performed. Therefore, the results demonstrate functional implementation and quantify computational overhead, but they do not establish superior cryptographic security. RC4 is retained only as an experimental legacy baseline because current standards deprecate its operational use. Future evaluation should include authenticated encryption, entropy and randomness testing, key-sensitivity analysis, repeated timing trials, and cryptographic hash verification of restored files.